Food and agriculture organization of the United Naitons. Commodity reports. Rice: 1960 (Rome Food and Agricultural Organization, 1960)
The rate of growth in rice production has slowed down in recent years, although it is still rising faster than population
Ref
Keywords: Agriculture; Rice trade